Ensino das doenças crônicas não transmissíveis no curso de graduação em Enfermagem - Maestri, Eleine (2016)
Through the need for general education there are policies, plans and programs aimed at certain scenarios, especially those focused on human resources training for the Sistema Único de Saúde of committed health with the health network and concerned with developing actions that aim to achieve the set national targets. It is considered extremely important to approach transversely content such as those belonging to the sphere of chronic diseases throughout the undergraduate courses in many different areas of health. The overall objective was to understand the process of teaching- learning of chronic noncommunicable diseases in an undergraduate degree in Nursing. As specific objectives, it is proposed: to know the main issues and recommendations to the process of teaching- learning for the training of professionals on chronic diseases published theses and dissertations of Nursing in the period after the National Curriculum Guidelines for undergraduate courses Nursing; Describe the curriculum components that address the teaching of chronic noncommunicable diseases and understand the form of the content selection on a course Undergraduate Nursing; Identify the methodologies used in the teaching of non-communicable chronic diseases in an undergraduate degree in Nursing. This is a qualitative research, case study method, performed in an undergraduate degree in nursing at a university in southern Brazil. The participants were fifteen students through group interview; eleven teachers through individual interviews, and documentary evidence of the pedagogical project of the course and eleven teaching plans. Data collection occurred from December 2015 to March 2016, following submission and approval by the Ethics and Human Research. For ordering and organizing the data, we used the Bardin (2011) content analysis with three stages: preanalysis, material exploration and treatment of results, inference and interpretation. The data analysis resulted in three central themes: Noncommunicable diseases: the production of Nursing graduate in Brazil; Contents related to chronic noncommunicable diseases developed in an undergraduate degree in nursing; and teaching methodologies used in addressing chronic diseases in undergraduate degree in Nursing. It is considered that in the teaching process are focused epidemiological needs of the region, but there are still gaps and weaknesses in the constitution of the education program, the selection of content and methodologies for the teaching of chronic noncommunicable diseases. Thus, it is suggested to educational institutions in Nursing: include in the teaching spaces plans for discussion and reflection on public health policies emphasizing the epidemiological needs, among them chronic non-communicable diseases; holding discussions and reflections between curriculum components for the cross approach to matters involving non-communicable diseases; providing training to teachers, including methodologies of active learning; and intensifying the education integration, service and community in addition to the training activities, research and strengthening the bond and reaching changes in reality.